Ultrafast chemical lithiation of single crystalline silicon nanowires: in situ characterization and first principles modeling - Seo, Jong-Hyun; Chou, Chia-Yun; Tsai, Yu-Hao; Cho, Yigil; Seong, Tae-Yeon; Lee, Woo-Jung; Cho, Mann-Ho; Ahn, Jae-Pyoung; Hwang, Gyeong S.; Choi, In-Suk (ROYAL SOC CHEMISTRY, 2015)
Through a combined density functional theory and in situ scanning electron microscopy study, we provide evidence of the ultrafast chemical lithiation of a single crystalline Si nanowire which is brought into direct contact with Li metal in the absence of an applied external electric field. Unlike the previous in situ lithiation results, the ultra-fast lithiation process in this study is purely driven by the concentration gradient and is found to be limited by Li diffusion through the pristine/lithiated Si phase boundary. The experimental and calculated lithiation speeds are in excellent agreement at around 1 mu m s(-1), corresponding to a high Li diffusivity value of about 10(-9) cm(2) s(-1). The improved understanding of lithiation kinetics may contribute to the design of higher-power Si-based anodes.
Keywords: SIZE-DEPENDENT FRACTURE; ELECTROCHEMICAL LITHIATION; LITHIUM; LI; ANODES; FILM; DELITHIATION; ELECTRODES; BATTERIES; DIFFUSION